Sustainable production and consumption: assessing the economic viability of traditional and organic yerba mate cultivation - Alceu Souza; Claudio Kapp Junior; Felipe Rafael Zarpellon; Claudimar Pereira da Veiga (Humanities & Social Sciences Communications)
Abstract In response to the growing consumer demand for organic products, this study examines the economic viability of traditional versus organic Yerba Mate (Ilex paraguariensis) cultivation in Paraná State, Brazil. The research uses a robust financial analysis framework to compare production expenses, projected profits, and associated risks over a fifteen-year horizon for a single hectare of land. The analysis employs the multi-index methodology to provide empirical evidence and analytical insights into the economic and risk profiles of both traditional and organic agricultural practices. This study further enhances the evaluation by incorporating the Monte Carlo Method and Crystal Ball software, transforming key financial indicators into stochastic variables. This approach allows for a nuanced risk assessment that captures the inherent uncertainties in agricultural investment. The findings indicate a significant economic advantage for organic farming, with an organic return on investment (ROI) of 12.03%, substantially outperforming the 3.99% ROI of conventional methods. Moreover, the research highlights the improved risk-adjusted returns of organic farming, showing an almost negligible probability of encountering a negative net present value (NPV), specifically P(NPV_organic ≤ 0) ≈ 0. The results underscore the financial viability and reduced risk of organic Yerba Mate cultivation, positioning it as a strategic alternative to traditional agricultural methods. These insights align with current market trends favoring sustainable and health-conscious consumer choices and provide critical guidance for stakeholders in the farming sector. This study contributes to the academic discourse on sustainable agriculture and offers practical implications for enhancing economic sustainability and resilience in farming practices.